Comparison of Valve Academic Research Consortium (VARC)‐2 and VARC‐3 Criteria for Bleeding Complications After Transcatheter Aortic Valve Replacement - Stephan Nienaber; Janosch Himken; Max Meertens; Victor Mauri; Samuel Lee; Jonathan Curio; Elmar Kuhn; Richard Nies; Kaveh Eghbalzadeh; Johannes Dohr; Stephan Baldus; Hendrik Wienemann; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The Valve Academic Research Consortium (VARC) has updated criteria for periprocedural bleeding after transcatheter aortic valve replacement. However, clinical validation of the VARC‐3 bleeding definition is scarce. The aim of this study was to evaluate incidence, associated variables, and clinical impact of VARC‐3 bleeding. Methods The study included 2227 patients with severe aortic stenosis undergoing transcatheter aortic valve replacement between 2018 and 2023 at the University Hospital Cologne. VARC‐3 bleeding during the index hospitalization were analyzed. Incidence, variables associated with bleeding, and impact on 30‐day mortality were evaluated by comparison to the VARC‐2 criteria. All data were prospectively collected. Results VARC‐3 bleeding was 2.5 times more prevalent than VARC‐2 (13.9% versus 34.4%), as VARC‐3 includes nonattributable blood loss >3 g/dL as a bleeding event. Chronic kidney disease, thoracotomy access, dual antiplatelet therapy (P<0.001 for all), and female sex (P=0.023) were variables associated with VARC‐3 bleedings. Type 3 bleeding (VARC‐3) was associated with an increased 30‐day mortality (hazard ratio [HR], 2.89 [95% CI, 1.35–6.19], P=0.006). VARC‐2 major and life‐threatening bleeding events were associated with increased 30‐day mortality as well (HR, 2.74 [95% CI, 1.26–5.95], P=0.011 and HR, 29.60 [95% CI, 17.42–50.30], P<0.001). Conclusions The VARC‐3 criteria present a refined classification for bleeding with prognostic relevance. However, the VARC‐2 criteria demonstrate precision and clear correlation with increasing mortality risk proportional to the severity of bleeding too, showing even greater predictive accuracy in the transfemoral cohort. These findings require further validation with similar or even larger patient cohorts.